Analysis of Learning Experience in Tourism Destinations on Improving Students' History Knowledge - Muhammad Taufik; Anisa; Geral Jayanto; Aisyah Ramdani (Gema Cendekia Institute, 2025)
This study analyzes the impact of the direct learning experience in tourism destinations on the improvement of students' historical knowledge. History learning in the classroom is often considered monotonous, limiting contextual understanding and information retention. Tourism destinations, such as historical sites, museums, or cultural relics, offer authentic environments rich in historical information and the potential for multisensory experiences. Through a quantitative approach, the study involved students from several high schools participating in educational tourism programs to specific historic sites. Data was collected through pre-tests and post-tests to measure improvements in historical knowledge, as well as questionnaires to evaluate students' perceptions of their learning experiences. Preliminary results showed that students who participated in educational tours experienced significant improvements in their historical knowledge compared to the control group. In addition, hands-on experience in historic locations has been shown to increase learning interest, facilitate a deeper understanding of concepts, and strengthen long-term memory. The implications of this study highlight the importance of integrating learning activities outside the classroom, particularly through educational tourism, as an effective strategy to enrich the history curriculum and create a more meaningful and memorable learning experience for students. This study recommends the further development of similar programs to support holistic and contextual history education.